Isolation, Characterization and Targeted Metabolic Evaluation of Endophytic Fungi Harbored in 14 Seed-Derived Hypericum Species - Henzelyová, Jana; Antalová, Michaela; Nigutová, Katarína; Logoida, Mariia; Schreiberová, Andrea; Kusari, Souvik; Čellárová, Eva (Planta Medica, 2020)
Medicinal plants of the genus Hypericum are rich sources of bioactive naphthodianthrones, which are unique in the plant kingdom, but quite common in fungal endophytes. Cultivable endophytic fungi were isolated from 14 different Hypericum spp. originating from seeds grown under in vitro conditions and further acclimated to outdoor conditions. Among 37 fungal isolates yielded from the aerial and underground plant organs, 25 were identified at the species level by the fungal barcode marker internal transcribed spacer rDNA and protein-coding gene region of tef1α. Ten of them were isolated from Hypericum spp. for the first time. The axenic cultures of the isolated endophytes were screened for the production of extracellular enzymes, as well as bioactive naphthodianthrones and their putative precursors by Bornträgerʼs test and HPLC-HRMS. Traces of naphthodianthrones and their intermediates, emodin, emodin anthrone, skyrin, or pseudohypericin, were detected in the fungal mycelia of Acremonium sclerotigenum and Plectosphaerella cucumerina isolated from Hypericum perforatum and Hypericum maculatum, respectively. Traces of emodin, hypericin, and pseudohypericin were released in the broth by Scedosporium apiospermum, P. cucumerina, and Fusarium oxysporum during submerged fermentation. These endophytes were isolated from several hypericin-producing Hypericum spp. Taken together, our results reveal the biosynthetic potential of cultivable endophytic fungi harbored in Hypericum plants as well as evidence of the existence of remarkable plant-endophyte relationships in selected non-native ecological niches. A possible role of the extracellular enzymes in plant secondary metabolism is discussed.
Keywords: Hypericum spp.; Hypericaceae; endophytic fungi; Bornträgerʼs test; HPLC-HRMS; anthraquinones; naphthodianthrones